Albendazole alone vs. albendazole and diethylcarbamazine combination therapy for trichuriasis - Windya Sari Nasution; Muhammad Ali; Ayodhia Pitaloka Pasaribu; Syahril Pasaribu; Chairuddin P. Lubis (Indonesian Pediatric Society, 2014)
Background Trichuris trichiura is one of the most commonsoil-transmitted helminths, estimated to infect l billion peopleworldwide. Several studies have compared the efficacies ofalbendazole and diethylcarbamazine, but the efficacy of acombination of these two drugs has been inconclusive.Objective To assess the effectiveness of a single dose ofalbendazole compared to a combination of albendazole anddiethylcarbamazine for trichuriasis treatment.Methods A randomized, clinical open trial was conducted fromJune to September 2009 on elementary school children withtrichuriasis from two villages in the North Sumatera Province.Stool specimens were collected at baseline and at days 7, 14,21, and 28 after treatment, and examined by the Kato Katzmethod. Subjects were randomized into two groups. Group Ireceived a single dose of albendazole (400 mg) and group IIreceived albendazole (400 mg) plus diethylcarbamazine (6 mg!kg). Statistical analyses used were Chi square test for cure ratesand Wilcoxon rank test for egg reduction rates.Results One hundred eight children were enrolled andrandomized into group l (53 children) and group II (55children). The prevalence of T. trichiura infection was 54.7%.There were no significant differences (P=0.52) in the curerate between groups I and II (66% and 60%, respectively) or inegg reduction rates at day 28 (54.5% and 60.07%, respectively,P= 0.10).Conclusion Albendazole alone and abendazole combinedwith diethylcarbamazine have similar efficacies for trichuriasistreatment, in terms of cure rates and egg reduction rates.